2011
DOI: 10.1039/c1cc11627d
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer drug cisplatin can cross-link the interdomain zinc site on human albumin

Abstract: Cisplatin, cis-[Pt(Cl 2 (NH 3 ) 2 ], can crosslink residues His67 of domain I and His247 of domain II in human albumin, occupying the major binding site for the essential metal zinc on the protein.Cisplatin is a widely used anticancer agent, particularly effective for treating solid tumors such as ovarian, testicular, bladder, head and neck cancers. 1 In vivo, cisplatin is converted to its active forms by aquation, 2 being highly reactive toward biomolecules such as DNA 3 and proteins. 4 Although DNA is prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 35 publications
1
67
0
2
Order By: Relevance
“…Binding of the divalent cation Co 2+ in serum is impaired in ischemic and systemic inflammatory states, and is proposed for semiquantitative monitoring of modification of plasma albumin [40–43]. Since the Zn 2+ binding sites in albumin include other divalent cations such as Cd 2+ and the multivalent cation cisplatin [44, 45], it likely that the same site is modifiable by ischemic and oxidant stress in hemorrhagic shock. In conjunction with the findings of the current study, these considerations suggest that persistence of impaired Zn 2+ binding state of the HMW plasma fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of the divalent cation Co 2+ in serum is impaired in ischemic and systemic inflammatory states, and is proposed for semiquantitative monitoring of modification of plasma albumin [40–43]. Since the Zn 2+ binding sites in albumin include other divalent cations such as Cd 2+ and the multivalent cation cisplatin [44, 45], it likely that the same site is modifiable by ischemic and oxidant stress in hemorrhagic shock. In conjunction with the findings of the current study, these considerations suggest that persistence of impaired Zn 2+ binding state of the HMW plasma fraction.…”
Section: Discussionmentioning
confidence: 99%
“…also found that cisplatin cross-links domains of albumin. 27 However, whether cisplatin can function as a cross-linking reagent has not been fully explored. Platinum(II) has a strong affinity for sulfur and nitrogen containing ligands, and the coordination sites are the side chains of methionine (Met), cysteine (Cys) and histidine (His), namely, thioether, sulfhydryl, and imidazole.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Theselected regions are shown in Figure 3. Crosslinking is destroyed upon CID fragmentation, producing adiscrete set of shorter, but still gold-bound fragments from which the original binding sites can be deduced, as observed in MS/MS studies of aplatinum-crosslinked peptide.…”
mentioning
confidence: 99%